HUBUNGAN RIWAYAT STATUS PEMBERIAN ASI EKSKLUSIF DENGAN PERTUMBUHAN OPTIMAL ANAK USIA PRASEKOLAH DI WILAYAH RW 03 KELURAHAN KEBON KACANG - Likha Mahabbah Sunnah Makkawang, (2023)
Breast milk is the most suitable nutrition for the needs of babies at birth. Optimal breastfeeding can be done by starting early breastfeeding initiation within the first 1 hour after the baby is born and exclusively breastfed until 6 months of age. Children who are exclusively or non-exclusively breastfed can be seen from the physical changes in child growth with changes in body weight, height, and head level. This study aims to analyze the relationship between breastfeeding status and optimal growth of children in RW 03 Kebon Kacang Village. The research design used quantitative research with a cross sectional approach. The sampling technique used total sampling technique as many as 67 respondents. Data analysis of this study used the Chi-Square test. The results of this study indicate that there is a relationship between breastfeeding status and optimal child growth with a p-value of 0.008 (<0.05). Therefore, it can be concluded that the history of exclusive breastfeeding status can affect children's optimal growth.